Below the zero lower bound: a shadow-rate term structure model for the euro area - Wolfgang Lemke; Andreea Liliana Vladu (European Central Bank (ECB), 2017)
We propose a shadow-rate term structure model for the euro area yield curve from 1999 to mid-2015, when bond yields had turned negative at various maturities. Yields in the model are constrained by a lower bound, but - as a special feature of our specification - the bound is allowed to change over time. We estimate that it has first ranged marginally above zero, but has decreased to -11 bps in September 2014. We derive the impact of a changing lower bound on the yield curve and interpret the impact of the September 2014 ECB rate cut from this perspective. Our model matches survey forecasts of short rates and the decline in yield volatility during the low-rate period better than a benchmark affine model. We estimate that since mid-2012 the horizon when short rates are expected to exceed 25 bps again has ranged between 18 and 62 months.
Keywords: C32; E43; E52; 330; lower bound; monetary policy expectations; nonlinear state space model; term structure of interest rates